A meta-analysis evaluating risk factors for compound free flaps for upper extremity defect reconstruction comparing complications and functional outcomes of compound free flaps with and without bone components - Zhang, Ying; Gazyakan, Emre; Hundeshagen, Gabriel; Fischer, Sebastian; Bigdeli, Amir Khosrow; Will-Marks, Patrick; Kneser, Ulrich; Hirche, Christoph (Microsurgery, 2021)
Background Compound flaps offer the advantage of one stage defect reconstruction respecting all relevant tissues and early functional recovery by optimal vascularity of all components. Due to its specific vascular anatomy and the three-dimensional donor site, compound flaps with bone components may result in higher complication rates compared to soft tissue compound flaps. The meta-analysis summarizes the available evidence and evaluates whether bone components are a risk factor for periprocedural complications in upper extremity multidimensional defect reconstruction. Method PubMed and Embase were searched for all publications addressing compound free flaps for upper extremity defect reconstruction with bone or soft tissue components published between January 1988 and May 2018. The methodological quality was assessed with the American Society of Plastic Surgeons Evidence Rating Scale for Therapeutic Studies. Flap loss, thrombosis rate, early infection, hematoma, seroma, as well as donor site complications were extracted and analyzed. Results Twelve out of 1157 potentially eligible studies (evidence-III) comprising 159 patients were finally included with publication bias for all summarized complication rates. Complication rates for flaps with/ without bone components were: total flap loss 5%, 95% CI = 3%-10% (6%/5%); partial flap loss 8%, 95% CI = 5%-15%, (9%/8%); arterial/venous thrombosis 7%, 95% CI = 4%-12%, (8%/5%)/14%, 95% CI = 9%-21% (16%/6%, P < .05) with higher risk for flaps with bone components; infection 6%, 95% CI = 3%-12% (6%/6%); hematoma 6%, 95% CI = 3%-11% (6%/5%); seroma 5%, 95% CI = 3%-10% (5%/5%); dehiscence 10%, 95% CI = 6%-17% (11%/9%). Conclusion Compound flaps for upper extremity defect reconstruction including bone components have a higher venous thrombosis rate compared to compound soft-tissue flaps.
Gesehen am 02.11.2023